Discovering Tipologi Kepemimpinan Demokratis Kepala Sekolah Untuk Membangun Budaya Integritas Guru Di Lembaga Pendidikan: Discovering Tipologi Kepemimpinan Demokratis Kepala Sekolah Untuk Membangun Budaya Integritas Guru Di Lembaga Pendidikan - Mifta, Miftahul Janah; Suwadi (Journal of Primary Education Research, 2024)
This article purpose to explain the findings of the Democratic Leadership Typology of School Principals in Building a Culture of Teacher Integrity in Educational Institutions. Syaefudin's research shows that the development of a culture of school integrity is caused by the typology of democratic leadership. The principal as the main leader has the responsibility to create a school environment that is transparent, fair and honest. This research uses a qualitative approach with the type of field research. The sources used in this research were school principals and teachers. The findings of this research are that this type of democratic leadership can build a culture of teacher integrity because with this type of leadership, integrity in teachers continues to be instilled in teachers by educational institutions to achieve and familiarize students with efforts to practice these values. contained in integrity. The implications of the results of this research show that schools have their own variations and uniqueness in each school, so that school culture refers to every school member being able to work together and uphold the beliefs, values ​​and assumptions they believe in. The principal's leadership type and secondary school culture are able to provide enthusiasm for teachers so that they can increase teacher integrity. The type of school principal leadership that applies a democratic type tends to make teachers feel valued and cared for by often by often asking for teachers' opinions or even involving teachers. in determining school policy.